'Islamic Art Curation in Perspective: A Comparison with East Asian Models through the Case of the Leeum Samsung Museum'. Issue 1 (23rd November 2018) - Gonzalez, Valerie
With the development of a global museum culture since the eighties, called 'curationism' by David Balzer, the question of how to show ancient art both in newly founded institutions and in refurbished historic displays, is more than ever relevant. As much as contemporary art, artistic heritage participates in the new cultural discourse defining nations and communities, channelled through world-class museums and galleries. In that context, the Islamic artistic traditions gained tremendous visibility, as venues like the Museum of the Islamic Art in Doha or the Louvre's new scenography in Paris, put these traditions on the forefront of the international stage. This article examines this museology in transcultural perspective, through a comparison between Islamic and Korean ceramics installations in the renovated Ashmolean Museum in Oxford, and in the Leeum, in Seoul. The former privileges an archaeological narrative, the latter an aesthetic phenomenological approach. In revealing a qualitative asymmetry between the exhibitory practices in the areas of Islamic and East Asian art, this comparison allows for further discussion about museological issues such as the tension between didacticism and aesthetics, or the competitive relationship between architecture, design, and art in the displays' space. Ultimately, the comparison posits East Asian experimentalism as a model from which to draw inspiration for reinventing the curation of Islamic art.